Climate-Friendly Seafood: The Potential for Emissions Reduction and Carbon Capture in Marine Aquaculture. (25th January 2022) - Jones, Alice R; Alleway, Heidi K; McAfee, Dominic; Reis-Santos, Patrick; Theuerkauf, Seth J; Jones, Robert C
Abstract: Aquaculture is a critical food source for the world's growing population, producing 52% of the aquatic animal products consumed. Marine aquaculture (mariculture) generates 37.5% of this production and 97% of the world's seaweed harvest. Mariculture products may offer a climate-friendly, high-protein food source, because they often have lower greenhouse gas (GHG) emission footprints than do the equivalent products farmed on land. However, sustainable intensification of low-emissions mariculture is key to maintaining a low GHG footprint as production scales up to meet future demand. We examine the major GHG sources and carbon sinks associated with fed finfish, macroalgae and bivalve mariculture, and the factors influencing variability across sectors. We highlight knowledge gaps and provide recommendations for GHG emissions reductions and carbon storage, including accounting for interactions between mariculture operations and surrounding marine ecosystems. By linking the provision of maricultured products to GHG abatement opportunities, we can advance climate-friendly practices that generate sustainable environmental, social, and economic outcomes.